The impact of technological development on transport enterprises’ marketing strategy (Lithuanian example) - Išoraitė, Margarita; Jarašūnienė, Aldona; Vaičiūtė, Kristina (Business: Theory and Practice, 2022)
The article analyses the influence of technological development of transport enterprises on marketing strategies in the light of academic literature which highlights the importance of technological development tools. Technological development of enterprises in the transport sector is necessary in order to adapt to technological, economic, and market changes. The article presents major technological developments which are considered significant according experts. The most important technological development tools which influence marketing strategies of transport enterprises are presented. In order to examine the tools of transport development, a qualitative analysis was performed, and the method of statistical analysis was applied. The research results can be applied in planning marketing strategies of transport enterprises.